Przeszkoda uprowadzenia kobiety oraz ciężka bojaźń po jej stronie w świetle wyroku Roty Rzymskiej c. Lefebvre z 24 maja 1969 r. - Góralski, Wojciech (Ius Matrimoniale, 2015)
The case regards the marriage of Maria and Wincety, who concluded the marriage on 15 June 1959. The woman claimed to have been kidnapped and, therefore, entered into the relationship without her consent. Little wonder that after eight days the couple was separated. Later, Mary filed a complaint regarding the invalidity of the marriage to the Campaign Tribunal on 27.10.1959 indicating two important invalidity titles: abduction, serious coercion and fear. On 6 March 1963 a negative sentence on both counts was passed, the plaintiff filed an appeal to the Appellate Tribunal of Vicariatus Urbis, which on 26 April 1968 issued a positive judgment for both the first and the second invalidity title. After filing the appeal by the defender of the marital bond, the case was considered by the Roman Rota Turnus c. Lefebvre. On 24 May 1969 the judgment was passed invalidating the marriage only with regard to the serious coercion and fear on the side of the plaintiff. Presenting and commenting on the Rota judgment the author places emphasis on the factual motivation.